MODEL PENDIDIKAN TASAWUF DALAM MEMBENTUK KARAKTER CINTA TANAH AIR DAN CINTA DAMAI DI ORGANISASI MAHASISWA AHLITH THORIQOH AL-MU’TABAROH AN-NAHDLIYAH UNIVERSITAS YUDHARTA - Maulidatur Riza Fauzia; Ahmad Ma’ruf (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2021)
Expert Student Organization Thoriqoh al-Mu'tabaroh an-Nahdliyyah Yudharta University which always strives to shape the character of nationalism, love for the homeland, and love of peace to its members. One of the goals of character building is as a form of realization of the vision and mission of the organization. The solution to shape this character is the existence of a Sufism education model that is applied by the matan organization itself. This study uses a qualitative type of research with a case study approach at the MATAN Organization, Yudharta University. Data collection techniques through, (1) observation, (2) Interview, and (3) Documentation. Furthermore, data analysis is done by (1) data condensation, (2) data display, and (3) data verification. The results of this study indicate that (1) the model of Sufism education in shaping the character of love for the homeland and love of peace in the MATAN organization uses Sufism education which emphasizes the akhlaqi model of Sufism education of Imam al-Ghazali, (2) The results obtained from the application of the model are: increased understanding of members related to Sufism education which is marked by the willingness of members to carry out Sufism teachings.